2015
DOI: 10.1097/mnm.0000000000000323
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of single-photon emission computed tomography combined with computed tomography in relation to MRI on osteochondral lesions of the talus

Abstract: MRI is the current standard for OLT diagnosis. SPECT/CT allows a three-dimensional localization of scintigraphic osteoblastic activity in the area of interest, providing additional information about the involvement of the subchondral bone and the vitality of the osteochondral lesion and the location of multiple lesions. We recommend the use of SPECT/CT and MRI together for comprehensive diagnostic assessment of OLT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 23 publications
0
11
0
3
Order By: Relevance
“…The addition of single photon emission computerized tomography (SPECT) imaging to CT adds to the diagnostic value of CT scanning by identifying co-existing pathology as well as showing the activity around the lesion of interest. [ 24 ] Recently Tamam et al [ 25 ] suggested that SPECT-CT is used in conjunction with MRI for the assessment of OLT. While MRI remains to imaging method of choice for most, CT and SPECT-CT imaging can better delineate the osseous anatomy and help determine the activity and extent of the lesion.…”
Section: Ct Scanmentioning
confidence: 99%
See 1 more Smart Citation
“…The addition of single photon emission computerized tomography (SPECT) imaging to CT adds to the diagnostic value of CT scanning by identifying co-existing pathology as well as showing the activity around the lesion of interest. [ 24 ] Recently Tamam et al [ 25 ] suggested that SPECT-CT is used in conjunction with MRI for the assessment of OLT. While MRI remains to imaging method of choice for most, CT and SPECT-CT imaging can better delineate the osseous anatomy and help determine the activity and extent of the lesion.…”
Section: Ct Scanmentioning
confidence: 99%
“…While MRI remains to imaging method of choice for most, CT and SPECT-CT imaging can better delineate the osseous anatomy and help determine the activity and extent of the lesion. For this reason, some now recommend the addition of SPECT-CT for the evaluation of OLT [ 25 ].…”
Section: Ct Scanmentioning
confidence: 99%
“…Asimismo, el SPECT-CT conforma una alternativa a la RM en caso de que la condición médica del paciente no permita su toma o ante la presencia de material de osteosíontesis. [20][21][22] Dentro del tratamiento quirúrgico se describen varias opciones: técnicas de estimulación de la médula ósea, reducción abierta y fijación interna, reemplazo articular con autoinjerto o aloinjerto y técnicas de regeneración articular, cada una con indicaciones y tasas de éxito variables. 2,23 El gold estándar aún es el debridamiento artroscópico y la realización de microfracturas con tasas de éxito cercanas al 85%.…”
Section: Discussionunclassified
“…Die Anwendung von neuen hybriden Bildgebungsverfahren wie SPECT/CT oder von multimodalen Bildfusionierungen (SPECT/MRT) könnte die diagnostische Genauigkeit verbessern (71,75,76). Die PET/MRT der Hände bei Patienten mit rheumatoider Arthritis ist technisch möglich und vereint zwei Methoden mit hoher Sensitivät und morphologischer Auflösung (76), ist jedoch noch in Entwicklung begriffen.…”
Section: Abb 7 Ankylosierende Spondylarthropathieunclassified